Dampak Pola Asuh Orang Tua Terhadap Gaya Interaksi Sosial Mahasiswa Bimbingan Penyuluhan Islam A Semester 6 Universitas Islam Negeri Sumatera Utara - Rizki, Putri Handayani; Balqhis, Amanda Nurul; Mardiyah, Ainul (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Social interaction is a crucial skill for university students, especially within academic environments that require effective collaboration and communication. This article aims to analyze the impact of parenting styles on the social interaction patterns of sixth-semester students majoring in Islamic Guidance and Counseling at the State Islamic University of North Sumatra. This study employs a qualitative approach using in-depth interviews with three students. The findings indicate that parenting styles that emphasize discipline, responsibility, attention, and open communication tend to produce students who are confident, open, and capable of building healthy social relationships. Conversely, authoritarian, restrictive, or unresponsive parenting styles often result in individuals who are withdrawn, lack self-confidence, and tend to isolate themselves from social environments. Therefore, parenting plays a significant role in shaping students' character and their social interaction styles in the academic setting. This study recommends the importance of balanced parenting as well as a supportive campus environment that fosters students’ social development, enabling them to grow into socially and emotionally mature individuals.